Patterns of Change: Forces and Motion. (2nd July 2016) - Phillips, Marianne; Jeffery, Tonya D.
ABSTRACT: Patterns of Change: Forces and Motion is an integrated science lesson that uses the 5E lesson cycle to tie together science with language arts, mathematics, literature, technology, engineering and social studies in an engaging format applicable for young learners. This lesson has been uniquely designed for the purpose of providing elementary teachers with ideas for using hands-on minds-on activities to foster inquiry and discussion, while engaging their students to use technology as a learning tool. This lesson has been used on the elementary level to teach students about the forces that have an effect on motion.